Reflections on the Degree of Technological (un)preparedness in the Country Evidenced by COVID-19... And what do we, Authors and Readers of Cadernos de Prospecção Magazine, have to do with it? - Suzuki, Henry (2020)
At the exact moment these lines are being typed, dozens of working groups are poring over projects for 3D printing respiratory valves, many of whom do not even know where they will be used. Several other teams are poring over do-it-yourself lung ventilator projects, with extensive media coverage. In the same vein, just yesterday, an article published on the website of the Chamber of Deputies commented on the “patent breach” and made reference to a body named “Instituto Nacional da Patrimônio Intellectual (INPI)” (sic). Without going into the merits of the intentions or the conceptual or spelling errors, some questions remain: a) How effective can such actions be, for example, in a context of production of highly complex medical equipment? b) Wouldn't it be better to learn, for example, from patents already published, from their inventors or holders? c) In addition to what is described in the patents themselves, how much more barriers are there to access components, materials and “know-how”? d) Wouldn't it be more effective to form partnerships with companies that produce devices that have already been tested and registered? Unfortunately, the impression one gets is that, with rare exceptions, we do not even address basic questions. Year after year, we observe deindustrialization and the loss of productive capacity in our country. In many areas, we have unlearned, even if simply (which is not that simple), how to reverse-engineer to copy or manufacture what already exists. Crisis situations, like the one we are experiencing today, only show our degree of technological (un)preparedness. And what do we, authors and readers of Cadernos de Prospecção, have to do with it? This is the question that is asked in order to carry out an individual reflection. Perhaps, more important than the answer itself is the act of questioning ourselves and, more than that, the attitude that each of us will have in the face of this crisis. In this context, the Journal Cadernos de Prospecção brings, in a pioneering way, a Special Edition with spontaneous contributions from authors focused on coping with the pandemic generated by the etiological agent Coronavirus, SARS-COV-2, which causes the disease COVID-19. In the short space of just three weeks, 59 manuscripts were received and underwent blind evaluation by two reviewers; then, by the evaluation of the Special Edition Committee and this whole process was finalized with the appreciation of the manuscripts by the Editorial Board. Of the 59 articles, 18 (31%) were accepted, 39 (66%) were rejected and 2 (3%) are still under evaluation for possible insertion in the Edition of volume 13, number 3, of June 2020. The Coronavirus section will continue to receive articles until this pandemic is extinguished, as new works will be inserted as they are accepted. The 18 articles that make up this Special Edition bring together contributions from 79 authors affiliated with 36 organizations from the academic, business and government sectors. Its topics include: current affairs, economics, policies, legislation, medical and personal protection equipment (respirators, masks, etc.), pharmaceuticals and clinical tests, as well as prospecting for articles and patents. We hope that the knowledge and invitations to the reflections gathered here can contribute to our society to face and come out of this pandemic strengthened!